Preservation in Paraffin Oil: Alternative for Fungi Preservation in Simple Laboratory Concept - Sem Samuel Surja; Gabi Vania Sally; Favian Sergius Ruby Hartoyo; Sandy Vitria Kurniawan; Yanto Budiman (Althea Medical Journal, 2020)
Background: A good collection of fungi culture can be maintained with good preservation methods. With appropriate methods, preservation can be performed in low-budget laboratories, such as with periodic subculture and preservation in either sterile water or in paraffin oil. The aim of this study was to assess the viability, morphology, contamination, and antifungal susceptibility profile of fungi preserved in sterile water or paraffin oil compared to a periodic subculture.Methods: This study was an experimental study using Aspergillus sp., Trichophyton mentagrophytes and Candida albicans. The fungi were preserved by a periodic subculture or in sterile water or in paraffin oil for six months. A comparison of viability, morphology, contamination, and antifungal susceptibility profile between methods were made before and after six months of study.Results: The viability of all the fungi was maintained in both periodic subculture and preservation with paraffin oil. However, the T. mentagrophytes was not viable in preservation using sterile water. All methods could maintain the morphology without contamination. There were reductions in the inhibition zone against antifungal drug in preservation with sterile water and paraffin oil.Conclusion: Preservation in paraffin oil is superior to preservation in sterile water in terms of maintaining fungal viability. This method is suitable for the use in a simple laboratory, albeit considerations should be given to the reduction of inhibition zone.